2019
DOI: 10.1093/biolre/ioz180
|View full text |Cite
|
Sign up to set email alerts
|

Women with polycystic ovary syndrome present with altered endometrial expression of stanniocalcin-1†

Abstract: Stanniocalcin-1 (STC-1) is a pro-survival factor that protects tissues against stressors, such as hypoxia and inflammation. STC-1 is co-expressed with the endometrial receptivity markers, and recently endometrial STC-1 was reported to be dysregulated in endometriosis, a condition linked with endometrial progesterone resistance and inflammation. These features are also common in the endometrium in women with polycystic ovary syndrome (PCOS), the most common endocrine disorder in women. Given that women with PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…In line with recent data on STC-1 expression in the normal human endometrium, our findings indicate that the endometrial epithelium is the main target of STC-1 localization, while the stroma is not ( 43 , 44 ). This also applies to hormone-dependent tumor tissues like breast and ovarian cancers underlying the role of STC-1, especially in adenocarcinoma development ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with recent data on STC-1 expression in the normal human endometrium, our findings indicate that the endometrial epithelium is the main target of STC-1 localization, while the stroma is not ( 43 , 44 ). This also applies to hormone-dependent tumor tissues like breast and ovarian cancers underlying the role of STC-1, especially in adenocarcinoma development ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 92%
“…In younger women with a more severe PCOS phenotype and higher BMI, STC-1 gene expression did not increase in the secretory phase as it did in the other groups. STC-1 protein expression increased from PE to LSE in stromal cells, but only in healthy women and not in those with PCOS, which is potentially indicative of a stromal cell defect in women with PCOS ( Khatun et al , 2020 ). Further investigation of eSCs challenged with cAMP, previously established as an inducer of STC-1 expression, has revealed that eSCs from healthy women displayed a strong increase in STC-1 expression ( Khatun et al , 2020 ).…”
Section: The Expression Pattern and Physiological And Pathophysiological Roles Of Stc-1 In The Mammalian Female Reproductive Systemmentioning
confidence: 89%
“…Endometrial STC-1 expression has been described in several mammals, including rats, pigs, sheep and horses ( Song et al , 2006 , 2009 ; Xiao et al , 2006 ; Kikuchi et al , 2011 ). STC-1 expression in the human endometrium has been more recently described ( Aghajanova et al , 2016 ; Khatun et al , 2020 ).…”
Section: The Expression Pattern and Physiological And Pathophysiological Roles Of Stc-1 In The Mammalian Female Reproductive Systemmentioning
confidence: 99%
See 2 more Smart Citations